1974
DOI: 10.1071/ea9740533
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sulphate on the selenium content of pasture plants

Abstract: In the three experiments reported, the selenium content of pastures was shown to be substantially affected by applications of sulphate fertilizer. Where pasture yields responded to sulphur topdressing, selenium levels in the legumes present were reduced by as much as 50 per cent due largely to yield dilution effects. On a second site, where pasture responses to sulphur were not obtained, selenium levels were also depressed, in this case indicating the existence of an antagonism between sulphur and selenium. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…Several researchers reported reductions in SeO 4 concentration in plant tissues ranging from 80% to 100% when sulfate level was increased in the growth medium (Leggett and Epstein 1956;Ulrich and Shrift 1968;Ferrari and Renosto 1972;Barak and Goldman 1997). Previous studies also showed that sulfate has a much greater eect on plant uptake of SeO 4 than SeO 3 (Pratley and McFarlane 1974;Gissel-Nielsen 1973). However, other than the results of this study, there are no data available describing the eects of increasing sulfate levels on SeMeth uptake and volatilization by (Abrams et al 1990).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Several researchers reported reductions in SeO 4 concentration in plant tissues ranging from 80% to 100% when sulfate level was increased in the growth medium (Leggett and Epstein 1956;Ulrich and Shrift 1968;Ferrari and Renosto 1972;Barak and Goldman 1997). Previous studies also showed that sulfate has a much greater eect on plant uptake of SeO 4 than SeO 3 (Pratley and McFarlane 1974;Gissel-Nielsen 1973). However, other than the results of this study, there are no data available describing the eects of increasing sulfate levels on SeMeth uptake and volatilization by (Abrams et al 1990).…”
Section: Discussioncontrasting
confidence: 56%
“…2, 4; Table 2). Previous research has shown that SeO 4 uptake and volatilization by plants are strongly inhibited by the presence of high concentrations of sulfate in the growth medium (Pratley and McFarlane 1974;Mikkelsen et al 1988;Mikkelsen and Wan 1990;Zayed andTerry 1992, 1994;Barak and Goldman 1997). Antagonistic sulfate/ selenate interactions have generally been reported in single cells, excised roots, and whole plants (Lauchli 1993).…”
Section: Discussionmentioning
confidence: 94%
“…The close relationship between Se(VI) and SO42-uptake by plants has been observed many times (Gissel-Nielsen et al, 1984;Mikkelsen et al, 1988b;Pratley and McFarlane, 1974). In general, increasing the concentration of SO ]-in the soil solution reduces Se accumulation by plants (Wan et al, 1988).…”
Section: Introductionmentioning
confidence: 93%
“…For example, increasing the intake of dietary Zn protects sheep against the onset of Cu toxicity (Bremner et al 1976) and it was suspected that Cu deficiency in sheep grazing near an industrial smelter was probably induced as a result of excessive intakes of Cd and Zn (Koh and Judson 1986). Sulfur and Se are similar chemically and hence are potentially antagonistic in their uptake in plants and their utilisation in animals (Prattley and McFarlane 1974;Pope et al 1979;Abdel-Rahim et al 1985).…”
Section: Dietary Interactionsmentioning
confidence: 99%